The importance of gender roles in human nutrition - Wright, Iain A. (International Livestock Research Institute, 2016)
Interview with Iain Wright (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684